Regulatory and functional divergence among members of Ibβfruct2, a sweet potato vacuolar invertase gene controlling starch and glucose content - Zhang, Kai; Wu, Zhengdan; Wu, Xuli; Han, Haohao; Ju, Xisan; Fan, Yonghai; Yang, Chaobin; Tang, Daobin; Cao, Qinghe; Wang, Jichun; Lv, Changwen (Frontiers in Plant Science, 2023)
Sweet potato [Ipomoea batatas (L.) Lam.] is an important food and industrial crop. Its storage root is rich in starch, which is present in the form of granules and represents the principal storage carbohydrate in plants. Starch content is an important trait of sweet potato controlling the quality and yield of industrial products. Vacuolar invertase encoding gene Ibβfruct2 was supposed to be a key regulator of starch content in sweet potato, but its function and regulation were unclear. In this study, three Ibβfruct2 gene members were detected. Their promoters displayed differences in sequence, activity, and cis-regulatory elements and might interact with different transcription factors, indicating that the three Ibβfruct2 family members are governed by different regulatory mechanisms at the transcription level. Among them, we found that only Ibβfruct2-1 show a high expression level and promoter activity, and encodes a protein with invertase activity, and the conserved domains and three conserved motifs NDPNG, RDP, and WEC are critical to this activity. Only two and six amino acid residue variations were detected in sequences of proteins encoded by Ibβfruct2-2 and Ibβfruct2-3, respectively, compared with Ibβfruct2-1; although not within key motifs, these variations affected protein structure and affinities for the catalytic substrate, resulting in functional deficiency and low activity. Heterologous expression of Ibβfruct2-1 in Arabidopsis decreased starch content but increased glucose content in leaves, indicating Ibβfruct2-1 was a negative regulator of starch content. These findings represent an important advance in understanding the regulatory and functional divergence among duplicated genes in sweet potato, and provide critical information for functional studies and utilization of these genes in genetic improvement.